DEVELOPMENT OFENERGY SECURITY TO SUPPORT MARITIME DEFENSE WITH THE UTILIZATION OF MICROALGAE AS BIODIESEL FOR COASTAL COMMUNITIES - Khotimah, Khusnul (Jurnal Pertahanan dan Bela Negara, 2018)
Abstract – Marine resources as energy resources has become one means for the construction maritime power and unifying the region's defense for Indonesia. The geographical condition of Indonesia as an archipelagic country with the vast majority of territorial waters, as well as its strategic cross-position, becomes a fundamental source for sustainable energy development through the utilization of microalgae as a potential marine plant for biodiesel fuel, a diesel mix for Indonesian coastal communities. The research method in this study uses literature study and observation of previous authors' research, which will result in an analysis of energy objectives as supporting maritime defense that includes: (1) comprehensive understanding on the management and development of marine energy resources through the use of biodiesel from renewable energy of marine microalgae; (2) raising effective awareness and cooperation among the coastal communities, government and industry regarding the greatness of Indonesian history that has been built from the control over the oceans as a source of defense in developing energy security to support maritime defense. Keywords: maritime power, energy security, microalgae